Prediction borderline personality disorders relay on negative life events - Khabir, Leila; FallahZadeh, Maryam; Mohamadi, Nourallah (International Journal of Applied Behavioral Sciences, 2015)
Background: Borderline personality disorder (BPD) is a chronic condition that warrants further empirical investigation. The aim of this research was investigated prediction of BPD symptomatology relay on recent life experience. Method and Materials: Data for the current study was collected from students of Shiraz university. Sample consisted of 120 undergraduate students. The ages of the sample ranged from 18-26 with an average age of 19.55. Forty-four participants were men (36.6%) and fifty-six participants were women (46.6%). Instruments were used in this study include: Inventory of College Students’ Recent Life Experience (ICSRLE; Kohn, Lafreniere, & Gurevich, 1990) and Five-Factor Borderline Personality Inventory (FFBI; Mullins-Sweatt et al., 2012). Results: revealed non-significant effects for gender on total borderline personality scores, five subscales of FFBI and negative life events. Also these results showed negative life events predicted borderline personality traits. Conclusion: Negative life events could predict borderline personality traits.